In silico models of the macromolecular NaV1.5-KIR2.1 complex - Stary-Weinzinger, Anna (Frontiers in Physiology, 2024)
In cardiac cells, the expression of the cardiac voltage-gated Na+ channel (NaV1.5) is reciprocally regulated with the inward rectifying K+ channel (KIR2.1). These channels can form macromolecular complexes that pre-assemble early during forward trafficking (transport to the cell membrane). In this study, we present in silico 3D models of NaV1.5-KIR2.1, generated by rigid-body protein-protein docking programs and deep learning-based AlphaFold-Multimer software. Modeling revealed that the two channels could physically interact with each other along the entire transmembrane region. Structural mapping of disease-associated mutations revealed a hotspot at this interface with several trafficking-deficient variants in close proximity. Thus, examining the role of disease-causing variants is important not only in isolated channels but also in the context of macromolecular complexes. These findings may contribute to a better understanding of the life-threatening cardiovascular diseases underlying KIR2.1 and NaV1.5 malfunctions.